The value of non-pollen palynomorphs in interpreting paleoecological change in the Great Basin (Nevada, USA). Issue 3 (20th March 2017) - Tunno, Irene; Mensing, Scott A.
Abstract: Non-pollen palynomorphs (NPPs) are identifiable microfossils that survive chemical digestion during pollen extraction and appear in pollen slides. They represent important proxies and indicators of environmental change that can be integrated with pollen studies of landscape history. NPPs have been widely studied in Europe since the 1970s and regularly included in paleoecological studies, whereas in the United States only the most common NPPs have been routinely tallied. The aim of this study is to contribute to the validation of the use of NPPs in the reconstruction of landscape history. We analyzed NPPs in modern and fossil sediment samples from Stonehouse Meadow, located in Spring Valley in the eastern part of central Nevada. We present a total of 64 modern and fossil NPPs, with images and morphological descriptions given for all previously unknown NPPs and a selection of the most important known NPPs. The comparison of pollen and NPPs in the fossil sediments improves our interpretation of the ecological changes of the last 8000 yr.